Machining of transparent brittle material by laser-induced seed cracks - Shanmugam, Naveenkumar (Kansas State University, 2015)
Transparent brittle materials such as glass and silicon dioxide have begun to replace the conventional materials due to the advantageous properties including high strength and hardness, resistance to corrosion, wear, chemicals and heat, high electrical isolation, low optical absorption, large optical transmission range and biocompatibility. However because these materials are extremely hard and brittle, development of an ideal machining process has been a challenge for researchers. Non-traditional machining processes such as abrasive jet and ultrasonic machining have improved machining quality but these processes typically results with issues of poor surface integrity, high tool wear and low productivity. Therefore a machining technique that overcomes the disadvantages of existing methods must be developed. This study focused primarily on improving the machinability and attaining crack-free machined surfaces on transparent brittle materials by inducing micro cracks or seed damages on the subsurface of the materials. The hypothesis was that micro-cracks induced by femtosecond laser would synergistically assist the material removal process by a cutting tool by weakening or softening the material, followed by conventional machining process. Laser induced damages due to varying laser intensities and at different depths in bulk BK7 glass was studied in order to select the optimal laser machining conditions for the experiments. Dimensional and structural profiles of laser cracks are observed using an optical microscope. A comparative study of machined untreated BK7 samples and damage induced BK7 samples was conducted. Due to its simple process kinematics and tool geometry, orthogonal machining is used for the study. Results showed that machining laser-treated samples caused an average 75% force reduction on comparison to machining of untreated samples. Laser treated machined samples were produced without subsurface damages, and reduced tool wear was noted. Overall improved machinability of BK7 glass samples was achieved.
Keywords: BK7 glass machining; Femtosecond laser cracks; Induced cracks; Laser assisted machining; Orthogonal machining; Transparent brittle material machining; Engineering (0537)